The building of Vṛndāvana: architecture, theology, and practice in an early modern pilgrimage town - Okita, Kiyokazu; Lutjeharms, Rembert (Brill's Indological library, 2024)
"The small town of Vrndavana is today one of the most vibrant places of pilgrimage in northern India. Throngs of pilgrims travel there each year to honour the sacred land of Krsnas youth and to visit many of its temples. The Building of Vrndavana explores the complex history of this town's early modern origins. Bringing together scholars from various disciplines to examine history, architecture, art, ritual, theology, and literature in this pivotal period, the book examines how these various disciplines were used to create, develop, and map Vrndavana as the most prominent place of pilgrimage for devotees of Krsna. Contributors are: Guy L. Beck, Mans Broo, David Buchta, John Stratton Hawley, Barbara A. Holdrege, Rembert Lutjeharms, Cynthia D. Packert, and Heidi Pauwels"--